Students’ perception of communication and collaboration effectiveness in online learning mathematics during the COVID-19 - Sri Supiyati; Muhammad Halqi; Ahmad Rasidi (Jurnal Elemen, 2022)
This study aims to determine student perceptions of the effectiveness of communication and collaboration in online learning mathematics during the COVID-19 pandemic. This study was an ex-post-facto with an exploratory, descriptive approach. The sample of this study was 26 students of the Mathematics Education Study Program at the Universitas Hamzanwadi. The respondents of this study were 26 students of Mathematics Education at Hamzanwadi University, five males and 21 females, which were obtained using the convenience sampling technique. This research was conducted in the even semester of the 2020/2021 academic year. The instrument used is a closed questionnaire with answers that are degraded according to the Likert scale and validated by experts. The research data were analyzed descriptively and inferential statistics. The results showed that (1) the perception of mathematics education students was 58% of students giving a negative response to every question about the effectiveness of communication and collaboration in online learning; (2) ineffective communication and collaboration in online learning with an average student perception score of 2.16; (3) there is a positive and significant relationship between communication and collaboration in online learning during the COVID-19 pandemic with a significance value of 0.000 which is smaller than the alpha test value of 0.05 (0.05); (4) the relationship of communication and correlation in online learning is strong or high with a correlation coefficient value of 0.677.